ASPECTOS ECOLÓGICOS E BIOLÓGICOS DE VESPAS E ABELHAS (INSECTA, HYMENOPTERA) QUE NIDIFICAM EM CAVIDADES PREEXISTENTES. - BUGGENHAGEN, TAYANE CRISTINA (2016)
The Atlantic Forest is one of the 35 "hotspots" to house one of the most diversified and threatened faunas and floras in the world. One of the main causes of the loss of biodiversity is the changes in habitats made by man, leading to the extinction of several species. In view of this, one of the concerns among scientists is to understand the effects of these changes on ecosystem processes, such as pollination, predation and parasitism. The biology of many animals living in these forests is still poorly known and many species can be extinct without even being described. The objective of this work was to investigate whether the cluster of wasps and bees that nest in preexisting cavities and associated parasitoids differs in two fragments of Atlantic Forest being one of them with constant management, and to bring information about the nesting biology of Ancistrocerus flavomarginatus and Auplopus ater. This study was carried out in fragments of the Atlantic Forest in the South of Paraná, one of them in the Reserva Natural do Patrimônio Natural (RPPN) and the other in a Reserva Legal (R. Legal), located in General Carneiro, Paraná. Each area received 256 trap nests of different diameters, where they were fixed at 1.5 meters from the ground and collected every 15 days, totaling one year of sampling. It was verified that both composition and diversity of wasps, bees and parasitoids was higher in R. Legal. The metrics of trophic networks were also analyzed and their values indicated that they are very similar areas and that the management carried out in R. Legal is not changing the development of this ecosystem. Biological aspects of Auplopus ater, a species of parasitic wasp of spiders and nesting in preexisting cavities have also been described.